UTILIZATION OF CHITOSAN FROM CRAFT SHELL WASTE (Portunuspelagicus) IN CREAM MANUFACTURING FACE MOISTURIZER - Yohannes Cavin Pranantha Pelawi; Merry Sukmiwati; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aims to determine the effect of adding different concentrations of chitosan solutions on the quality of facial moisturizing creams and to find out how much chitosan concentration is appropriate to add to the quality of facial moisturizing creams. The treatments given were different concentrations of chitosan, namely 1% (K1), 2% (K2), 3% (K3). The parameters used in this study were yield test, water content, ash, nitrogen and degree of deacetylation in determining the quality of chitosan and pH test, emulsion stability test, humectant test and viscosity test to determine the quality of facial moisturizing cream. The results of this study showed that the chitosan obtained from the crab shells waste had the form of powder particles, with 12 % of yield, 9.6% of moisture content, 6.7% of ash, 4.54% of nitrogen; and 73.74% of the degree of deacetylation. The best treatment was the addition of 3% (K3) chitosan concentration with a 5.20 pH value; 99.54% of emulsion stability, 65.32% of humectant, and 38.045cPs Viscosity. Keyword:Chitosan, facial moisturizing cream, small shell crab